Care-paradigm shift promoting smoking cessation treatment among cancer center patients via a low-burden strategy, Electronic Health Record-Enabled Evidence-Based Smoking Cessation Treatment. Issue 6 (17th July 2019) - Ramsey, Alex T; Chiu, Ami; Baker, Timothy; Smock, Nina; Chen, Jingling; Lester, Tina; Jorenby, Douglas E; Colditz, Graham A; Bierut, Laura J; Chen, Li-Shiun
Abstract : Patients with cancer who smoke were more likely to be assessed and treated for tobacco use as part of their cancer care than when referred to a specialist. Abstract: Tobacco smoking is an important risk factor for cancer incidence, an effect modifier for cancer treatment, and a negative prognostic factor for disease outcomes. Inadequate implementation of evidence-based smoking cessation treatment in cancer centers, a consequence of numerous patient-, provider-, and system-level barriers, contributes to tobacco-related morbidity and mortality. This study provides data for a paradigm shift from a frequently used specialist referral model to a point-of-care treatment model for tobacco use assessment and cessation treatment for outpatients at a large cancer center. The point-of-care model is enabled by a low-burden strategy, the Electronic Health Record-Enabled Evidence-Based Smoking Cessation Treatment program, which was implemented in the cancer center clinics on June 2, 2018. Five-month pre- and post-implementation data from the electronic health record (EHR) were analyzed. The percentage of cancer patients assessed for tobacco use significantly increased from 48% to 90% ( z = 126.57, p < .001), the percentage of smokers referred for cessation counseling increased from 0.72% to 1.91% ( z = 3.81, p < .001), and the percentage of smokers with cessation medication significantly increased from 3% to 17% ( z = 17.20, p < .001). EHR functionalities may significantly address barriers to point-of-care treatment delivery, improving its consistent implementation and thereby increasing access to and quality of smoking cessation care for cancer center patients.